Book review: Little Hungarian Fruit Growing - Surányi, D. (International Journal of Horticultural Science, 2020)
There is a part in the history of agriculture that deals with all the past issues of fruit growing, which also deals with the material and intellectual values of fruit species. Just as history is a science, so historical fruit-growing works in so many ways, so does frontier science…Presumably, different issues are important to today’s fruit growers than those dealing with the past and historicity of fruit growing. The distinction between historical fruit production and the history of fruit production is justified because of differences in aims and methods. However, examining and explaining certain issues can yield economically useful results.